Therapeutic writing as a means to increase the metacognitive knowledge of students during the production of writing - Παπατρέχα Βιργινία; Σπαντιδάκης Ιωάννης; Βασιλάκη Ελένη; Μιχαηλίδη Ελένη (Education Sciences, 2019)
The aim of this research is to design, implement and evaluate an interventional program that combines the teaching of writing strategies with the therapeutic-writing techniques of students with or without learning difficulties in order to ascertain the interaction between the quality of the students’ writing and metacognition. Four groups of 12-year-old high school students took part in the research project. Three experimental groups and one control group: the first experimental group, implemented socio-cognitive intervention, the second experimental group, implemented therapeutic writing techniques intervention, the third experimental group, implemented a combination interventional program (socio-cognitive models of writing and therapeutic writing techniques), in the control group, was applied the "traditional" teaching method of writing, as defined by the curriculum. The results confirmed the beneficial effects and the importance of combining the teaching writing strategies with therapeutic writing techniques, contributing to enhancing students’ thinking, communicating, feeling (cognitive, metacognitive and emotional dimension) in the process of constructing meaning.